Comparison of Different Injector Nozzles for the Utilization of Polyoxymethylene Dimethyl Ethers - Rieß, Sebastian; Fuchs, Thorsten; Strauß, Lukas; Günthner, Michael; Wensing, Michael (SAE Technical Papers, 2024)
Oxygenated substances are a promising approach in the field of alternative fuels. A current example of such a fuel are Polyoxymethylene Dimethyl Ethers (OME). With their physical and chemical properties, alternative fuels like OME pose new challenges for diesel engine injection systems. As the heating value is low compared to conventional Diesel fuel, measures must be taken to increase the amount of fuel injected. Possible solutions include increasing the nozzle hole diameter, the injection pressure, and the number of nozzle holes. All mentioned adaptions have an influence on the mixture formation and make it necessary to examine the injection process in detail also with regard to phenomena such as cavitation. In this study, three passenger car Diesel injector nozzles are compared, two of which are adapted in terms of nozzle hole diameter (increase by 20%) and number of nozzle holes (increase from 8 to 12) in order to increase the mass flow rate of fuel to the required elevated level. The injectors are examined under various operating conditions using the optical measurement methods of Mie scattering and Schlieren photography in a constantly purged high-temperature and -pressure injection chamber. Mixture formation is analyzed on basis of the measurement results for different fuels and blends. Results show that adaptions such as increasing the nozzle hole diameter or the number of nozzle holes are unavoidable, as increasing the injection pressure alone cannot realistically compensate for the lower calorific value of OME. In addition, strong cavitation can be observed without adjustments to the nozzle holes. With the adapted nozzles, increasing the nozzle hole diameter leads to an increase in the local fuel/air ratio, while increasing the number of nozzle holes leads to a decreas
Keywords: Air / fuel ratio; Dimethyl ether (DME); Diesel / compression ignition engines; Alternative fuels; Diesel fuels; Imaging and visualization; Fuel injection; Nozzles